Utilizing Almond Oil with Vitamin E as an Alternative Fixative to Formalin - Sachdev, Sanpreet Singh; Chettiankandy, Tabita Joy; Sardar, Manisha Ahire; Kende, Prajwalit Prakash; Gaikwad, Rajesh Prabhakar; Fernandes, Lynette Custodio (Annals of Pathology and Laboratory Medicine, 2022)
Introduction: The health hazards resulting from exposure to formalin have given rise to the need of developing safer alternative fixatives. Almond oil has been widely used in the aromatherapy and cosmetic industry for its good penetrating and skin-rejuvenating properties, whereas vitamin E is a widely known anti-oxidant. The present study aimed to test the fixative efficacy of almond oil with vitamin E as compared to formalin. Material and Methods: The present study was conducted on 42 tissue specimens obtained by crown lengthening procedure or other minor surgical procedures. The specimens were divided into two groups- 21 specimens in the study group were fixed in oil fixative while others were fixed in formalin for 24 hours. Routine histopathological procedures were done and the histomorphological parameters related to the preservation of tissue architecture as well as cellular details were assessed. Result: The preservation of tissue architecture and cellular details in tissues fixed in AO were comparable to that of tissues fixed in formalin. Although statistically non-significant, all the three investigators agreed that oil-fixed tissues exhibited superior nuclear details as compared to formalin. Conclusion: Almond oil with vitamin E can be effectively used for the fixation of tissues, providing results that are comparable to formalin-fixed tissues. The non-toxic, non-irritant chemical nature of almond oil coupled with its ease of availability, enable it to be utilized safely even in remote areas